Kazakhstan Economic Update, December 2020 : A Slow Recovery Through the COVID-19 Crisis - World Bank (World Bank, Washington, DC, 2021)
The fallout of the Coronavirus (COVID-19) pandemic has hit the economy more than the crises in 2008 and 2015. The pandemic is projected to shrink by 2.5 percent this year. The economy is expected to grow modesty by 2.5 percent next year, based on an improved global economic outlook. This report estimates Kazakhstan’s poverty rate will increase to 12-14 percent in 2020 from a baseline of 6 percent Nevertheless, there are significant risks because of uneven economic recovery across countries due to the protracted pandemic and higher debt-related risks to the global financial market. The domestic financial sector is also exposed to a higher risk of growing non-performing loans if support measures are withdrawn.